2016
DOI: 10.1007/s13205-016-0544-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and screening of l-asparaginase free of glutaminase and urease from fungal sp.

Abstract: l-Asparaginase is a chemotherapeutic drug used in the treatment of acute lymphoblastic leukaemia (ALL), a malignant disorder in children. l-Asparaginase helps in removing acrylamide found in fried and baked foods that is carcinogenic in nature. l-Asparaginase is present in plants, animals and microbes. Various microorganisms such as bacteria, yeast and fungi are generally used for the production of l-asparaginase as it is difficult to obtain the same from plants and animals. l-Asparaginase from bacteria causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 27 publications
1
35
0
4
Order By: Relevance
“…In the present study dextrose proved to have a positive effect on l-asparaginase biosynthesis by the test organism as it increased the production level of this enzyme. Other authors also reported that dextrose increases the production of l-asparaginase as in case of Aeromonas sp., Aspergillus terreus (Amena et al 2010;Doriya and Kumar 2016;El-Hefnawy et al 2015;Gurunathan and Sahadevan 2011;Varalakshmi and Raju 2013). However, other carbohydrate sources were reported for their enhancing effect on l-asparaginase biosynthesis as in case of sucrose and sorbitol for Streptomyces tendae (Kavitha and Vijayalakshmi 2010) and lactose in case of E. coli (Bahrani 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study dextrose proved to have a positive effect on l-asparaginase biosynthesis by the test organism as it increased the production level of this enzyme. Other authors also reported that dextrose increases the production of l-asparaginase as in case of Aeromonas sp., Aspergillus terreus (Amena et al 2010;Doriya and Kumar 2016;El-Hefnawy et al 2015;Gurunathan and Sahadevan 2011;Varalakshmi and Raju 2013). However, other carbohydrate sources were reported for their enhancing effect on l-asparaginase biosynthesis as in case of sucrose and sorbitol for Streptomyces tendae (Kavitha and Vijayalakshmi 2010) and lactose in case of E. coli (Bahrani 2016).…”
Section: Discussionmentioning
confidence: 99%
“…L-ASNase produced by the A. terreus strain S-18 showed low L-GLUase activity (0Á15 U g À1 ), indicating that the enzyme of eukaryotic origin has an advantage over the Escherichia coli native L-ASNase (EcASNase 2) that has notable L-GLUase activity (Campbell and Mashburn 1969;Wriston and Yellin 1973). Studies have demonstrated the production of L-ASNase with low L-GLUase activity from eukaryotic sources (Huang et al 2014;Doriya and Kumar 2016), although some studies have shown that L-GLUase activity is important for the overall efficacy of treatment and serves as a positive modulator of L-ASNase activity in sub-micromolar concentrations of asparagine in the serum of patients undergoing treatment (Anishkin et al 2015). Therefore, A. terreus strain S-18 presents as a new L-ASNase eukaryotic source.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated the production of l ‐ASNase with low l ‐GLUase activity from eukaryotic sources (Huang et al . ; Doriya and Kumar ), although some studies have shown that l ‐GLUase activity is important for the overall efficacy of treatment and serves as a positive modulator of l ‐ASNase activity in sub‐micromolar concentrations of asparagine in the serum of patients undergoing treatment (Anishkin et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Phenol red was pH indicator which would be turned to yellow at acidic pH and turn into pink at alkaline pH. The released ammonia will change the color of the medium from yellow to pink indicating the enzymatic activity due to different nitrogen sources (Doriya & Kumar, 2016;Phang et al, 2018;Sudhir et al, 2012).…”
Section: Isolation and 16s Rrna Analysismentioning
confidence: 99%